COVD-25. THE PARADOXICAL EFFECTS OF COVID-19 ON CANCER CARE IN THE NEURO-ONCOLOGY SETTING. (9th November 2020) - Cort, Nicole; Broom, Alex; Kenny, Katherine; Page, Alexander; Durling, Jennifer; Brown, Casey; Lipp, Eric; Ashley, David; Walsh, Kyle; Johnson, Margaret; Khasraw, Mustafa
Abstract: COVID-19 has caused ongoing interruptions to healthcare systems worldwide, shifting care to virtual platforms, and placing significant economic and logistical burdens on clinical practice. The pandemic has created uncertainty in delivering the standard of care, both in areas of cancer diagnosis and treatment, especially within neuro-oncology. Due to the pandemic, care and operational planning goals have shifted to infection prevention, modifying recommendations to decrease viral transmission and increasing telemedicine use, potentially creating a burden on implementing evidence-based medicine. These dynamics have since begun to redefine traditional practice and research regimens, impacting the comprehensive care that cancer patients can and should receive; and the enduring consequences for the delivery of healthcare. The impact of COVID-19 on oncology practice and trials might endure well beyond the short- to mid-term of the active pandemic. Therefore, these shifts must be accompanied by improved training and awareness, enhanced infrastructure, and evidence-based support to harness the positives and offset the potential negative consequences of the impacts of COVID-19 on cancer care. To address these paradoxical effects, we will conduct iterative, qualitative (face-to-face/video conference) interviews with neuro-oncology clinical and research professionals and adult brain tumor patients receiving care during the pandemic. We will capture unique aspects of oncology care: the lived, subjective, situated, and contingent accounts of patients and medical professionals, especially during a pandemic. We will also specifically compare the impact of telehealth during the pandemic on delivery of care to complex neuro-oncology patients. A summary of this in-depth, qualitative approach will result in a sophisticated understanding of neuro-oncology care on the frontline at a time of crisis, as experienced during a pandemic, to articulate best practices for future implementation.